2021
DOI: 10.1080/13691058.2021.1909142
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision making for HIV pre-exposure prophylaxis (PrEP) with black transgender women

Abstract: Shared decision making is a collaborative process intended to develop a treatment plan that considers both the patient's preferences and the health provider's medical recommendations. It is one approach to reducing healthcare disparities by improving patientprovider communication and subsequent health outcomes. This study examines shared decision making about HIV pre-exposure prophylaxis (PrEP) with Black transgender women in Chicago, Illinois, USA, given high prevalence of HIV and disparities in PrEP use. Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…These barriers to PrEP are exacerbated for Black trans women and are of particular concern given that Black trans women are disproportionately affected by HIV [ 21 ]. A recent meta-analysis found that Black trans women compared to white trans women and trans women of all other races had a significantly higher HIV prevalence estimate [ 22 ] and the National HIV Surveillance System reported that the majority (51%) of all new HIV diagnoses among trans women in the United States are among Black trans women [ 23 ]. The risk of HIV infection for Black trans women and other trans women of color is highly affected by the intersection of discrimination and stigma they face due to sexism, racism, homophobia and transphobia [ 11 ] This intersectionality of discrimination and oppression results in both high HIV prevalence as well as barriers to and trust in HIV prevention methods such as PrEP [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These barriers to PrEP are exacerbated for Black trans women and are of particular concern given that Black trans women are disproportionately affected by HIV [ 21 ]. A recent meta-analysis found that Black trans women compared to white trans women and trans women of all other races had a significantly higher HIV prevalence estimate [ 22 ] and the National HIV Surveillance System reported that the majority (51%) of all new HIV diagnoses among trans women in the United States are among Black trans women [ 23 ]. The risk of HIV infection for Black trans women and other trans women of color is highly affected by the intersection of discrimination and stigma they face due to sexism, racism, homophobia and transphobia [ 11 ] This intersectionality of discrimination and oppression results in both high HIV prevalence as well as barriers to and trust in HIV prevention methods such as PrEP [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…41 Provider bias has also been found to negatively influence shared decision-making in adults with diabetes, 42 veterans with mental health care needs, 43 and adults who identify as lesbian, gay, bisexual, or transgender. 44-46…”
Section: Discussionmentioning
confidence: 99%
“…Despite the decision to adopt PrEP being complex, there are limited studies that have investigated the decisional needs of Black patients who are asked to consider adopting PrEP for HIV prevention 31 . The main objective of this study was to assess the decisional support needs of Black patients who are offered PrEP for HIV prevention.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been demonstrated in clinical trials across various populations and health domains, [24][25][26][27][28] but has only recently received attention in HIV prevention. 29,30 Despite the decision to adopt PrEP being complex, there are limited studies that have investigated the decisional needs of Black patients who are asked to consider adopting PrEP for HIV prevention 31 . The main objective of this study was to assess the decisional support needs of Black patients who are offered PrEP for HIV prevention.…”
Section: Introductionmentioning
confidence: 99%